Long bright river - Moore, Liz, 1983- (Riverhead Books, 2020)
"A suspense novel that also looks at the anatomy of a Philadelphia family rocked by the opioid crisis and the relationship between two sisters--one, suffering from addiction, who has suddenly gone missing amid a series of mysterious murders; the other a police officer who patrols the neighborhood from which she disappeared: a story about the formidable ties between place, family, and fate" --